(untitled) (Research, Society and Development, 2023)
Parasitic infections are a primary disease affecting wild animals in captivity, which can cause morbidity and even mortality. The study aimed to identify the prevalence of enteroparasites at the Brasília Zoo, Brazil, and their possible risk factors. The research was conducted in 2019, and 37 primates from 19 species participated. Three stool samples were collected from the enclosures and were processed using three parasitological methods: (i) Spontaneous sedimentation, (ii) Rugai, and (iii) Kato-Katz method. Soil samples were collected from five points in each enclosure and processed using the Spontaneous sedimentation method. Water samples were collected from drinking fountains and analyzed for the presence of enteroparasites, using the Spontaneous sedimentation method, and for thermotolerant coliforms and Escherichia coli using the COLILERT microbiological method. The results showed that 54% of the stool samples were positive, mostly for the commensal parasite Entamoeba coli. All soil samples were contaminated, mainly by the pathogenic protozoan Giardia sp. The presence of thermotolerant coliforms was detected in all water samples. This was the first study carried out on the prevalence of intestinal parasites in primates kept at the Brasília Zoo. It is essential for the health and well-being of animals kept in captivity, parasitological monitoring, as the identification of these parasites helps in the treatment and monitoring of infections, in addition to avoiding infections of people who work directly with them.